Relationship between hypertension during dialysis and body composition in non-overweight/overweight obese patients - Jiaoyan Chen; Xianqiong Lu; Jurong Yang; Jingrong Peng; Maodi She; Yunyan Wang (PLoS ONE, 2026)
Body composition parameters (such as BMI and waist-to-hip ratio) have a certain predictive value for blood pressure. In patients undergoing maintenance hemodialysis (MHD), BMI can affect dialysis adequacy and blood pressure control levels, and there are differences in body composition at different BMI levels. The aim of this study was to investigate the association between hypertension during dialysis and body composition in non-overweight/overweight obese patients. A total of 248 patients undergoing maintenance hemodialysis (MHD) at this center were enrolled. Body composition was measured using an InBody bioelectrical impedance analyzer prior to dialysis. Intra-dialysis blood pressure data from the preceding three months were collected via the hemodialysis system. Patients were categorized based on their dry weight at enrollment: those with BMI < 23 kg/m² were classified as the non-overweight group, and those with BMI ≥ 23 kg/m² as the overweight/obese group. LASSO regression was employed to identify body composition variables associated with hypertension during hemodialysis. Based on LASSO regression results, multivariate linear regression and logistic regression analyses were conducted to evaluate the impact of pre-dialysis body composition on blood pressure (BP) in non-overweight and overweight/obese hemodialysis patients. The overall prevalence of hypertension was 86% (214/248), and the proportion of overweight/obese patients was 41.0% (102/248). TBW and Protein were positively correlated with hypertension in non-overweight male patients (OR (95% CI): 1.28 (0.34–1.98); OR (95% CI): 1.97 (1.51–3.33)), and BMC was negatively associated with hypertension in non-overweight male patients (OR (95% CI): 0.10 (0.01–0.70)). In overweight obese female patients, Fat was positively associated with hypertension (OR (95% CI): 1.12 (1.01–2.26)). This study identified risk factors for elevated blood pressure associated with gender and BMI in a subset of the MHD Asian population. The study also provided evidence that different body composition factors (such as total body water, protein, bone mineral content, and fat) drive hypertension risk in different MHD subgroups, rather than being determined solely by BMI.